Implementasi Distribution Requirements Planning (DRP) di PT Wira Citra Agung Mandiri - Vicky Avinas; Didit Damur Rochman (Widyatama University, 2026)
The gap between increasing demand and limited supply is due to government policies that regulate the purchase and storage of subsidized LPG. This condition requires distribution agents to have an inventory management system that is able to adjust needs appropriately and sustainably. PT Wira Citra Agung Mandiri as a 3KG LPG distribution agent in Bandung Regency is experiencing problems in stock management and product distribution. Symptoms of problems that arise are characterized by frequent shortages of inventory at the base and shop level when demand increases, as well as excess stock in certain periods. This condition occurs because the inventory management implemented is still reactive and not yet supported by a structured and integrated distribution planning system, thus having an impact on logistics efficiency and service quality to consumers. This research aims to describe the implementation of ongoing logistics management and evaluate the usefulness of the Distribution Requirements Planning (DRP) model as an alternative distribution planning system in optimizing 3KG LPG supplies. The research method used is quantitative descriptive with analysis units of agents, bases and stalls which are members of the company's distribution network. Data was analyzed by comparing the Lot for Lot and Distribution Requirements Planning (DRP) methods in inventory management. The research results show that the application of DRP is able to produce distribution planning that is more systematic, coordinated and efficient than the Lot for Lot method. Apart from that, DRP has been proven to be able to reduce total inventory costs and overcome stock shortage problems significantly. Therefore, the implementation of DRP is recommended to be implemented comprehensively at PT Wira Citra Agung Mandiri in order to increase distribution efficiency and operational sustainability of 3KG LPG.